Preparation and properties of B2O3-Doped Ba(Zr 0.07Ti0.93)O3 ceramics - P. Jarupoom (2018)
In this work, barium zirconate titanate (Ba(Zr0.07Ti 0.93)O3) ferroelectric ceramics doped with B 2O3 were prepared by the conventional mixed-oxide method. The properties of the ceramics as a function of sintering temperature were investigated. Various technique such as X-ray diffraction (XRD) technique, scanning electron microscopy, dielectric permittivity spectroscopy and ferroelectric property measurement were used to obtain characteristic of the ceramics. The optimum density was observed for 1250 °C sintered sample. An increase in sintering temperature produced a decrease in dielectric constant. However, ferroelectric behavior was improved in 1275 °C sintered sample. The results were discussed in term of microstructure and crystallinity of the ceramics. © 2008 Trans Tech Publications, Switzerland.